The Differences in the Stimulation and Personal Social Development of School-Aged Children between Children WHO Raised by their Grandparents and Parents Respectively - Praba Diyan Rachmawati (Journal of Global Pharma Technology, 2016)
Introduction: Indonesia is a country that has a cultural feature related to child care. Grandparents can act as a parent because of unexpected factors such as the parents dying, accidents, illness, the parents being dependent on drugs, imprisonment, studying abroad or the parents still being adolescents. The aim of this research was to determine the difference between the stimulation and personal-social development of school-aged children taken care of by their grandparents and parents respectively. Method: The sample used consisted of 20 children taken care of by their grandparents and 30 children taken care of by their parents in one of the Elementary Schools in Surabaya. The independent variable was stimulation and the dependent variable was personal-social development. The data was collected using a questionnaires that was analyzed using Chi-Square and Spearman rho’s with significance α<0.05.  Results: The results showed there to be a significant difference in stimulation between grandparents and parents (p=0.007) and the same in personal social development between the grandparents and parents (p=0.000). There was no correlation between grandparent stimulation (p = 0.209) and parental stimulation (p= 0.244) with the personal social development of the school-aged children. Discussion: The personal social development of school-age children who are cared for by their grandparents was lower than those cared for by their parents. However, there was no relationship between the stimulation carried out by the grandparents and the personal social development as well as the stimulation given by their parents on the personal social development. Further research is suggested to analyze the factors that influence the stimulation and personal-social development of school-aged children by comparing the results of the grandparents’ children and those of the parents.Keywords: Grandparents, Parents problems of early childhood, Personal social development, School-aged children, stimulation.